Production and characterization of agricultural waste natural fiber-filled polylactic acid composites - Sen, Ibrahim; Sever, Kutlay (Springer, 2025)
The objective of this study was to obtain new composites containing polylactic acid (PLA) with artichoke stem (AP) at concentrations of 1%, 3%, 5%, 7%, and 10% by weight using a twin-screw extruder. The composites were created using biodegradable PLA and postharvest agricultural waste AP. The study aimed to determine whether these composites could be used. Thermal, mechanical, and morphological characterization of AP and these composites were performed. The findings of the study revealed that AP particles exhibited chemical and physical properties similar to other natural fibers. When incorporated into composites, these materials showed increased density and elastic modulus. However, decreases in tensile strength, elongation at break, and unnotched Izod impact were observed. Dynamic mechanical analysis revealed that PLA exhibited higher storage modulus (E ') values compared to AP-filled composites at 40 degrees C. In the differential scanning calorimetry analysis, while there was a slight fluctuation in the glass transition temperature (Tg) in the AP-filled composites, significant increases in the crystallinity degree (Xc) were observed when looking at the values of PLA. The results of the thermal gravimetric analysis showed that both Tmax and Ts values of the composite decreased as the AP content in PLA increased. Furthermore, SEM imaging of the composites containing P5AP clearly demonstrated the presence and distribution of AP particles within the PLA matrix.
Keywords: Polylactic acid (PLA); Natural fiber; Agricultural waste; Biocomposite; Characterization; Mechanical and thermal properties